Trust as a Protective Buffer: The Moderating Role of Interpersonal Trust in the Relationship Between Subjective Well-Being and Stress in Gen Z - Rahmatulloh, Ainurizan Ridho; Rinaldi, Martaria Rizky (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
Abstract: Generation Z faces an unprecedented mental health paradox: despite high digital connectivity, they report record levels of stress and declining subjective well-being (SWB). While the link between SWB and stress reduction is well-documented, the social moderators that facilitate this relationship remain under-explored. This study examines the moderating role of trust in the SWB-stress nexus among 267 undergraduate digital natives. Using moderation regression analysis, we demonstrate that trust serves as a critical protective amplifier. Our findings reveal that higher levels of trust significantly enhance the efficacy of SWB in mitigating stress, whereas low trust diminishes this protective effect. This suggests that interpersonal reliability is a prerequisite for psychological resilience in Gen Z. These results advocate for a shift in mental health interventions from purely individualistic self-care to the cultivation of social cohesion and trust-building within educational and social institutions Keywords: generation z, stress, subjective well being, trust